India : Selected Issues. (IMF Staff Country Reports; Country Report, 1998)
This Selected Issues paper on India reviews the revenue impact of tax reforms implemented by the central government since 1991. The paper highlights that since 1991, tax reforms have been an integral part of economic reforms in India. Following a blueprint laid out by a Tax Reforms Committee, the system of central government taxation has been streamlined as rates have been reduced and rationalized, while some base-broadening measures were implemented and new tax categories have been introduced. The paper also examines the issues related to foreign exchange markets.